Integrative-Interconnective Approaches in Al-Islam and Muhammadiyah Education: Advancing the SDGs at UMS - Hartono; Islah Gusmian; Giyoto (Profetika: Jurnal Studi Islam, 2025)
Objective: This study examines the implementation of Al-Islam and Kemuhammadiyahan (AIK) with an integration-interconnection approach at the University of Muhammadiyah Surakarta (UMS) and its contribution to SDG 4 (quality education), SDG 16 (peace and justice), and SDG 17 (global partnership). Theoretical framework:  The theoretical framework is based on KH Ahmad Dahlan's thoughts on modern Islamic education, the concept of integration-interconnection of knowledge, contextual curriculum theory, the warning of "normal science", and the AIK policy as a compulsory course in PTM. Literature review: AIK is seen as a praxis of educational values that shape Islamic character, although it still faces a dichotomy of science. Integration-interconnection is believed to make AIK more transformative, in accordance with the ideas of Brady and Kuhn. The relevance of AIK is increasingly evident in the context of SDGs 4, 16, and 17. Methods: The research uses a descriptive-qualitative method based on literature studies with primary data (Muhammadiyah policy, AIK curriculum, learning practices) and secondary data (academic literature). The analysis follows the Miles & Huberman model, with validity maintained through credibility, transferability, dependability, and confirmability. Results: The results of the study show that the application of AIK based on integration-interconnection in UMS can produce learning that is not only a transfer of knowledge, but also a transfer of values. AIK directs students to a comprehensive understanding that includes cognitive, affective, and psychomotor aspects. This model is relevant to Muhammadiyah's vision of modern Islamic education that progresses and supports the achievement of SDG 4 (quality education), SDG 16 (peace and justice), and SDG 17 (global partnership). Implications: It is necessary to reconstruct the AIK curriculum to be transformative and contextual, to strengthen the identity of PT Muhammadiyah, improve the quality of education, foster student character, and support sustainable development.  Novelty: The novelty of this research lies in the association of AIK based on integration-interconnection in UMS with the achievement of the SDGs, so that AIK is positioned not only as a typical Islamic course of Muhammadiyah, but also as a strategic instrument for inclusive and sustainable global education development.